1998
DOI: 10.1590/s0100-06831998000200002
|View full text |Cite
|
Sign up to set email alerts
|

Condutividade hidráulica de amostras remoldadas de um latossolo roxo distrófico tratado com água/vinhaça

Abstract: RESUMOEste trabalho foi realizado no CENA/USP, Piracicaba, SP, com a finalidade de obter informações relativas aos efeitos da aplicação de água/vinhaça (nas dosagens de 100, 200, 400, 800 e 1.000 m 3 ha -1 ) na condutividade hidráulica de amostras remoldadas de um Latossolo Roxo distrófico, sob condições saturadas e não saturadas. Empregou-se, para tanto, um infiltrômetro de carga constante, para a avaliação da condutividade hidráulica em solo saturado e, na caracterização da condutividade hidráulica em solo n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
1
0
3
Order By: Relevance
“…From the dose of 300m 3 h -1 , the value of K 0 was below the mean (1.91cm h -1 ) reaching the value of 1.4cm h -1 (Figure 2). In a way, for this soil, it can be said that the vinasse showed an effect of reducing the easiness in which water moves, which, somehow, comes against the values obtained by LOBATO et al (1998). These authors evaluated the variation of hydraulic conductivity of saturated soil of a dystrophic purple latosol with vinasse doses ranging from 0 to 1000m 3 ha -1 , and observed that the additions of vinasse doses promoted a decrease in the values of hydraulic conductivity of saturated soil.…”
Section: Hydraulic Conductivitymentioning
confidence: 95%
“…From the dose of 300m 3 h -1 , the value of K 0 was below the mean (1.91cm h -1 ) reaching the value of 1.4cm h -1 (Figure 2). In a way, for this soil, it can be said that the vinasse showed an effect of reducing the easiness in which water moves, which, somehow, comes against the values obtained by LOBATO et al (1998). These authors evaluated the variation of hydraulic conductivity of saturated soil of a dystrophic purple latosol with vinasse doses ranging from 0 to 1000m 3 ha -1 , and observed that the additions of vinasse doses promoted a decrease in the values of hydraulic conductivity of saturated soil.…”
Section: Hydraulic Conductivitymentioning
confidence: 95%
“…Estudos sobre este tema permitem o entendimento e a predição do fluxo de água no solo, que se constitui num parâmetro importante nos projetos de irrigação e drenagem, além de avaliações quanto à poluição e conservação do solo e da água (Lobato et al, 1998), temperatura e trafegabilidade do solo (Puckett et al, 1985), modelagem ambiental e ecológica (Tomasella et al, 2003).…”
Section: Introductionunclassified
“…Uma das fontes de erro na determinação da condutividade hidráulica pelo método do perfil instantâneo está na utilização de K 0 na equação, pois ele se altera a cada inundação, devido a alteração na distribuição das partículas do solo e também varia de acordo com o conteúdo de água inicial no solo (FALLEIROS et al, 1998;LOBATO;LIBARDI;CAMARGO, 1998).…”
Section: Análise Estatística Dos Resultadosunclassified